Job attitudinal behavior and job performance among public employees in Malaysia (A case study of Malaysia Co-operative Society Commission) / Norhayati Nayan - Norhayati, Nayan (2012)
Job performance has been identified as the significant key for organizations to gain competitive advantage and superior productivity. Many studies have conceptualized job performance as a multidimensional construct, however researchers have thus far provided inconclusive agreement on what factors should be included in measuring job performance. Since job attitudinal behavior is one of the area of concern for public employees, the purpose of this paper is to explore job attitudinal behavior variables such as affective commitment, self-efficacy, job characteristics and work engagement and its relationship with job performance among public employees in Malaysia. It also elaborates the extent to which Organizational Citizenship Behavior (OCB) mediates the above mentioned relationship. This research found that there was a positive correlation between job characteristics and job performance, and OCB was found to partially mediates the above mentioned relationship. However affective commitment, self-efficacy and work engagement was not found to have significant relationship with job performance.